Salt Marketing Strategy in Lombok Timur Regency, Nusa Tenggara Barat - Mohammad Subhan; Prawita Anggeni; Sirrul Hayati (Department of Aquaculture, 2021)
Marketing is the main problem felt by salt farmers in East Lombok Regency, especially during the harvest season, which has an impact on the conversion of the salt pond land to cultivation land. This research aims to: 1) identify salt marketing channels in East Lombok Regency, 2) develop salt marketing strategy in East Lombok Regency. This research uses qualitative methods and the data will be analyzed by SWOT analysis.Efficient salt marketing occurs when the marketing channels include producers (salt farmers)-cooperatives /micro, small and medium enterprises-consumers, because it can shorten marketing channels and-reduce operational costs. Marketing of salt in East Lombok Regency can be carried out with several strategies, namely: 1) Maximizing the role of cooperatives and micro, small and medium enterprises in salt marketing, 2) Improving the quality of human resources in managing the salt business, 3) Formulating regulations on salt trading, and 4) Providing production technology training to salt farmers and salt micro, small and medium enterprises.